Early career researchers want Open Science - Farnham, A; Kurz, C; Öztürk, M; Solbiati, M; Myllyntaus, O; Meekes, J; Pham, T; Paz, C; Langiewicz, M; Andrews, S; Kanninen, L; Agbemabiese, C; et al. (BioMed Central, 2017)
Open Science is encouraged by the European Union and many other political and scientific institutions. However, scientific practice is proving slow to change. We propose, as early career researchers, that it is our task to change scientific research into open scientific research and commit to Open Science principles.